Biochemical Prospects of Various Microbial Pectinase and Pectin: An Approachable Concept in Pharmaceutical Bioprocessing - Satapathy, Sonali; Rout, Jyoti Ranjan; Kerry, Rout George; Thatoi, Hrudayanath; Sahoo, Santi Lata (Frontiers in Nutrition, 2020)
Both pectin and pectinase are vitally imperative biomolecules in the biotechnological sector. These molecules are a feasible non-toxic contrivance of nature with extensive applicative perception. Understanding pectic substances and their structure, unique depolymerisation and biochemical properties such as catalytic mechanism and strong interrelationship among these molecules could immensely enhance their applicability in industries. For instance, gaining of knowledge with respect to these versatile molecular heterogenecity of the compounds could be considered as the center of concern to resolve the industrial issues from multiple aspects. In the present review, an effort has been made to orchestrate the fundamental information related to structure, depolymerization characteristics and classification of pectin as well as types and biochemical properties of pectinase. Furthermore, various production methods related to the optimization of product and significant contribution in the pharmaceutical industry (either pectinase or derived pectic substances) are described within this article.